2022
DOI: 10.1152/ajpheart.00204.2022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of COVID-19 pathogenesis in diabetes

Abstract: Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) virus, is a global pandemic impacting 254 million people in 190 countries. Comorbidities, particularly cardiovascular disease, diabetes, and hypertension, in-crease the risk of infection and poor outcomes. SARS-CoV-2 enters host cells through the angio-tensin converting enzyme 2 (ACE2) receptor, generating inflammation and cytokine storm, often resulting in multi-organ failure. The mechanisms and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 180 publications
0
34
0
2
Order By: Relevance
“…This novel form of COVID-induced diabetes with anomalous glycemic parameters and heightened rates of DKA (diabetic ketoacidosis), occurs in severely ill patients with higher mortality rates and poorer outcomes compared to COVID-19 patients with pre-existing diabetes ( Chandrashekhar Joshi and Pozzilli, 2022 ). The underlying pathobiological mechanism for this induced diabetes in COVID-19 patients has not been clearly delineated although it is suspected that SARS-CoV-2 could damage the beta cells of the pancreas and precipitate insulin resistance ( Aluganti Narasimhulu and Singla, 2022 ). There are some plausible mechanisms that underlie this new diabetes onset.…”
Section: Mechanisms Of Emerging Pasc Pathogenesesmentioning
confidence: 99%
“…This novel form of COVID-induced diabetes with anomalous glycemic parameters and heightened rates of DKA (diabetic ketoacidosis), occurs in severely ill patients with higher mortality rates and poorer outcomes compared to COVID-19 patients with pre-existing diabetes ( Chandrashekhar Joshi and Pozzilli, 2022 ). The underlying pathobiological mechanism for this induced diabetes in COVID-19 patients has not been clearly delineated although it is suspected that SARS-CoV-2 could damage the beta cells of the pancreas and precipitate insulin resistance ( Aluganti Narasimhulu and Singla, 2022 ). There are some plausible mechanisms that underlie this new diabetes onset.…”
Section: Mechanisms Of Emerging Pasc Pathogenesesmentioning
confidence: 99%
“…The composition of the MPs as to the cell origin was not different between normal and diabetic plasma, but the MP count was significantly increased in each subpopulation in patients with diabetes. The increased MPs observed in these patients with diabetes could be attributed to their hyperglycemia and obesity states, the two recognized risk factors associated with increased production of inflammatory cytokines and reactive oxygen species ( 2 , 6 , 24 ). The median age of control group is a little bit older than diabetic group, but we do not consider this small difference in age has a significant effect on the large difference in MP quantity identified between groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study provided visual evidence of MP release from activated ECs and adherent neutrophils in intact microvessels of diabetic rats ( 32 ). Clinical studies indicated that the circulating levels of MPs in patients with diabetes are correlated with the hyperglycemic state ( 2 , 53 , 58 , 59 ). To investigate the role of diabetes-associated MP increase in the development of severe forms of COVID-19, this study selected blood samples from normal subjects and patients with type 2 diabetes with poor glycemic control (HbA1c between 6% and 9%).…”
Section: Discussionmentioning
confidence: 99%
“…Although ACE2 seems to be the principal receptor for SARS-CoV-2 entry, studies suggest that DPP-4 also interacts with the novel coronavirus [ 10 , 27 , 28 ]. Recent reviews and in silico analyses propose that several receptors such as DPP-4, DPP-6, DPP-10, TLR4, C-lectin type receptors (CLRs), neuropilin-1 (NRP1) may interact with the SARS-CoV-2 receptor-binding domain [ 11 , 29 , 30 ].…”
Section: Virus-dpp-4 Interactionmentioning
confidence: 99%